2018
DOI: 10.5114/hivar.2018.76378
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B reactivation after HCV treatment with sofosbuvir/ledipasvir in a HIV-coinfected patient with previous positive anti-HBs antibody: a case report and a review of literature

Abstract: Chronic hepatitis B (HBV) and C (HCV) coinfection are frequently observed in clinical practice. The interaction between HCV and HBV is complex and not completely understood, and usually results in the suppression of hepatitis B replication by HCV superinfection or coinfection. Cases of hepatitis B reactivation during and after HCV treatment with direct acting antivirals (DDA) have been described, and it is recommended to screen all patients starting DAA therapy for HBV infection markers and to monitor those th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 20 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…As outline in methods, 'five different degrees of reactivations can be discriminated among the 32 patients with some form of reactivation: HBV DNA becoming detectable, HBsAg sero‐reversion with HBsAg becoming positive, clinical evident reactivation with rise in ALT, or need for initiation of antiviral therapy, and finally persistent HBsAg with or without death or transplant'. HBV DNA becoming positive was reported in all 32 patients but was intermittently positive with spontaneous resolution in all 19 cases from cohort series (with caveat that 2 patients were lost to follow‐up) and in 2 cases from case series 24,33 , while in 4 patients from case reports 23,25,27,32 , HBV DNA resolved likely partially due to early initiation of HBV antiviral therapy. HBsAg sero‐reversion was reported in no patient from cohort studies but found in 11 of 13 patients published as cases reports and being only intermittently positive in 3 of the 11 patients.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…As outline in methods, 'five different degrees of reactivations can be discriminated among the 32 patients with some form of reactivation: HBV DNA becoming detectable, HBsAg sero‐reversion with HBsAg becoming positive, clinical evident reactivation with rise in ALT, or need for initiation of antiviral therapy, and finally persistent HBsAg with or without death or transplant'. HBV DNA becoming positive was reported in all 32 patients but was intermittently positive with spontaneous resolution in all 19 cases from cohort series (with caveat that 2 patients were lost to follow‐up) and in 2 cases from case series 24,33 , while in 4 patients from case reports 23,25,27,32 , HBV DNA resolved likely partially due to early initiation of HBV antiviral therapy. HBsAg sero‐reversion was reported in no patient from cohort studies but found in 11 of 13 patients published as cases reports and being only intermittently positive in 3 of the 11 patients.…”
Section: Resultsmentioning
confidence: 93%
“…Of the 32 patients who had HBV reactivation, 13 patients had additionally a transient hepatitis, 1 patient had persistent HBV DNA 22 , and 12 patients had HBsAg sero‐reversion. Of the twelve patients with HBsAg sero‐reversion, 6 had transient hepatitis 22‐25,27,32 , 3 had persistent HBV DNA 28,31,34 , and another three had either a fatal outcome 29,30 or needed a liver transplantation 26 (Table 2); 19 patients had neither evidence of hepatitis, sero‐conversion nor any clinical sequelae.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations